IMPACT OF NON-FORMAL EDUCATION ON THE EFFICACY OF SCHOOL LEARNING - Cristina TABACARU (Moldova State University, 2018)
The paper is presenting an attempt to visualise how out-of-school learning could be dealt with in the in-school system and if it could enhance the content required by formal education. Study aims and hypothesis are to highlight the impact of non-formal activities on learning results as well as the importance of linking non-formal to formal education and cognitive, attitudinal and affective aspects of non-formal learning. The question the research is posing refers to how closely related to learning outcomes is the choice of reframing school activities in a non-formal approach We run a psychosocial survey based on a questionnaire elaborated by us in compliance with validity and reliability criteria. The questionnaire aimed to identify teachers' opinion regarding the impact and the efficiency of non-formal activities on learning outcomes. The present study researches how one can effectively link in-school and out-of-school learning. IMPACTUL EDUCAȚIEI NON-FORMALE ASUPRA EFICACITĂȚII ÎNVĂȚĂRII ȘCOLARE În lucrare am încercat să vizualizăm modul în care învățarea în afara școlii ar putea fi abordată în sistemul școlar și dacă aceasta ar putea îmbunătăți conținutul cerut de educația formală. Scopurile și ipotezele studiului constau în evidențierea impactului activităților non-formale asupra rezultatelor învățării, precum și a importanței legăturii dintre educația formală și formală și aspectele cognitive, atitudinale și afective ale învățării non-formale. Întrebarea pe care o prezintă cercetarea: Cât de strâns legată de rezultatele învățării este alegerea de a reface activitățile școlare într-o abordare nonformală? Efectuăm un sondaj psihosocial bazat pe un chestionar elaborat de noi în conformitate cu criteriile de validitate și fiabilitate. Chestionarul vizează identificarea opiniei profesorilor cu privire la impactul și eficiența activităților non-formale asupra rezultatelor învățării. Este studiat modul în care se poate conecta eficient învățarea în școală și în afara școlii.